Two new Indian hyphomycetes - U. BRAUN2, V.B. HOSAGOUDAR1 and (Indian Phytopathology, 2002)
Periconiella perseae-macranthae sp.nov. on Persea macrantha and Stenella cinnamomi sp.nov. on Cinnamomum sulphuratum are described from India.